Global Citizenship Development: Effects of Study Abroad and Other Factors - Kishino, Hinako; Takahashi, Tomoko (Journal of International Students, 2019)
The present study examined the development of global citizenship traits in undergraduate students at a liberal arts college in Southern California. Two hundred and sixty-eight students participated in a survey that measured their global citizenship traits. Using a cross-sectional correlational design, the study examined the experience and development of the students as they strive to become global citizens. The results indicated that students face challenges and a sense of discomfort during study abroad, but their global citizenship traits tend to improve after return. Additionally, the study explored students’ perceptions of the curriculum, co-curricular activities, and campus life characteristics. The quantitative analyses suggested that the college’s mandatory study abroad program offers students an opportunity to seek their global citizenship identities.